Ultrasound screening for pyelectasis in pregnant women. Clinical necessity or “art for art’s sake”? - Szkodziak, Piotr (J Ultrason, 2018)
Renal pelvicalyceal dilatation is caused by urine retention in the upper urinary tract. It is referred to as pyelectasis in medical literature. This term does not indicate the cause that leads to the dilatation of and urine retention in the renal pelvicalyceal system. Mild pelvicalyceal dilatation during pregnancy is usually considered to be physiological in nature – it can occur in up to 90% of pregnant women. Retention is more common in the right kidney, in primigravidae, in the second half of pregnancy and in multiple pregnancies. Pyelectasis during pregnancy rarely causes clinical symptoms and often does not require treatment. Nevertheless, urine retention in the renal pelvicalyceal system is conducive to the development of asymptomatic bacteriuria and may be a risk factor for recurrent urinary tract infections, pyelonephritis and acute kidney failure; it may also cause renal colic. In consequence, this condition can lead to intrauterine infection and premature labor in the pregnant woman and to prematurity, anemia, congenital pneumonia or sepsis in the child. In a study conducted at the 3(rd) Department of Gynecology of the Medical University of Lublin it was concluded that unilateral pyelectasis of more than 20 cm(3) is associated with a significant increase in the risk of asymptomatic bacteriuria. This volume corresponds to grade 3 and/or 4 pelvicalyceal dilatation according to the Society for Fetal Urology/European Federation of Societies for Ultrasound in Medicine and Biology classification. The pyelectasis volume measuring method using three-dimensional ultrasound scanning included in the criteria for the assessment of asymptomatic bacteriuria was assessed as sensitive and specific. The ultrasound-based evaluation of the kidneys for the presence of pyelectasis and its grade in pregnant women has some clinical implications. It allows for identifying cases with an increased risk of asymptomatic bacteriuria, which requires treatment in pregnant women. Screening during pregnancy for pyelectasis seems to be important in preventing asymptomatic bacteriuria from progressing to symptomatic urinary tract infection.